The Motor Boys in Mexico; Or, The Secret of the Buried City - Young, Clarence; Nuttall, Charles, 1872-1934 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Motor Boys in Mexico; Or, The Secret of the Buried City" by Clarence Young is a fictional adventure novel written in the early 20th century. The story follows three boys$1 (BNed, Bob, and Jerry$1 (Bwho embark on a journey from Arizona to Mexico after learning about a buried city rumored to hold great treasures. Their journey is filled with encounters both amusing and perilous as they deal with old enemies and new challenges along the way. At the start of the narrative, the boys are living in a mining camp in Arizona when a familiar figure, Professor Uriah Snodgrass, gets himself trapped in an abandoned mine shaft while collecting specimens. After rescuing the professor, he reveals the tale of a buried city in Mexico, igniting their curiosity. The boys decide to make the trip in their automobile, despite the looming threat of Noddy Nixon, a former nemesis, who they discover may also be heading to Mexico. The opening chapters set the tone for a mix of adventure and humor, foreshadowing the various challenges they will encounter on their quest. (This is an automatically generated summary.)s
Release date is 2013-07-12
E-text prepared by Donald Cummings and the Online Distributed Proofreading Team
Keywords: Automobiles -- Juvenile fiction; Automobile travel -- Juvenile fiction; Extinct cities -- Juvenile fiction; Mexico -- Juvenile fiction; Brigands and robbers -- Juvenile fiction